Hukum dalam Perspektif Islam dan Kapitalisme - Abu Yazid Adnan Quthny (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2017)
In making the law as a guideline together in social systems, there is a pattern of significant differences between the law-making which is based on the spirit of capitalism, in the spirit of making laws based on the Islamic spirit. So as to see which laws are based on capitalism, and which are based on Islamic law, Certainly not as easy as it seems. But of the existing laws in the social system, one can read the true interests behind a legal product. If the laws more near to acomulation capital with the exclusion of the national interest, then certainly produced legal products is legal in the perspective of capitalism.